The studies on mechanisms and applications of gamma-typed iron-oxides suspensions - Varut Emudom (Journal of Current Science and Technology, 2015)
Magnetized particle agglomerates (MPA) suspensions can be modeled as monodisperse suspensions of hard, magnetic spheres in a Newtonian continuous phase. The application of a magnetic field to the MPA suspensions causes the rearrangement of particles leading to a new structure. This structure has been observed to form under quiescent conditions and is described as consisting of chains or columns of particles spanning the gap of two diamagnetic parallel plates. Most fibrous aggregates still remain intact during shearing. This shear rate can be considered to be close to a critical value of 0.5 s-1 such that the fibrous structure can be strained or unstrained reversibly without any rupture of the fibrous structure. At shear rate higher than the critical value, most of columnar structures begin to break into small portions. Applications of magnetized particles are also investigated in which pipe flow experiments were performed using magnetized particles as additive agents to the flow medium. Pipe flow friction can be controlled using ferromagnetic materials in the form of gamma-typed iron oxides Fe2O3. Substantial friction reduction can be achieved with appropriate choice of operating parameters. Friction in pipe flow could be reduced as much as 80% with optimal operating parameters such as particle size, mass concentration, intensity of magnetization, and Reynolds number. The approximate ranges can be, for the initial exploratory testing, 30-50 microns in particle diameter, 2% in mass concentration, 1000 Gauss (G) for initial magnetization of particles, and 60,000 to 100,000 in Reynolds number.